Adding Nocturnal Advanced Practice Providers to an Academic Inpatient Neurology Service Improves Residents' Educational Experience. (April 2023) - Yu, Andrew T.; Jepsen, Nicole; Prasad, Sashank; Klein, Joshua P.; Doughty, Christopher
Background and Objectives : In the inpatient academic medical center, increased demand for clinical services often equates to an increased workload for trainees, which could have a positive or negative impact on their educational experience. In 2020, our academic medical center hired Advanced Practice Providers (APPs) to provide continuous additional overnight coverage for our neurology ward teaching service. We hypothesized that adding APPs and reducing overnight clinical workload for residents would have a positive impact on resident education.Methods : We performed a mixed-methods, prospective study that included needs-assessments by residents, semi-structured interviews with both residents and APPs, and surveys to residents and nursing staff. In addition, we collected quantitative data such as hours of sleep, number of admissions, and number of pages to capture the impact of APPs on resident overnight shifts.Results : The addition of APPs overnight increased the median hours of sleep overnight from 1 hour to 3 hours ( P < .001) and decreased the median number of pages overnight from 31.5 to 17 ( P < .001). The median number of patients the resident was responsible for cross-covering overnight decreased from 24 patients to 14 patients ( P < .001). The majority of resident responses (94%) agreed that the addition of APPs benefited their education by reducing workload and increasing time allotted to reading and formulating plans for overnight admissions. 88% of residents agreed that the addition of APPs improved quality of life and reduced risk of burnout.Conclusion : Advanced Practice Providers significantly reduced resident workload, leading residents to report improvements in the educational experience overnight and reduced perceived risk of burnout.